2015
DOI: 10.1371/journal.pone.0135264
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity Study of Clinical Ultrasound Imaging on Lateral Curvature of Adolescent Idiopathic Scoliosis

Abstract: BackgroundNon-ionizing radiation imaging assessment has been advocated for the patients with adolescent idiopathic scoliosis (AIS). As one of the radiation-free methods, ultrasound imaging has gained growing attention in scoliosis assessment over the past decade. The center of laminae (COL) method has been proposed to measure the spinal curvature in the coronal plane of ultrasound image. However, the reliability and validity of this ultrasound method have not been validated in the clinical setting.ObjectivesTo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 32 publications
1
48
1
Order By: Relevance
“…Ultrasound technique was firstly used in this study to assess the spinal flexibility on the patients with AIS and a high feasibility was found. The reliability and validity of using ultrasound to assess scoliosis has been well established previously [ 15 17 ], which agrees with this study: a good correlation between the ultrasound and radiographic assessment (r = 0.77). It is also found that the curve angle assessed by ultrasound was lower than that assessed by X-ray.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ultrasound technique was firstly used in this study to assess the spinal flexibility on the patients with AIS and a high feasibility was found. The reliability and validity of using ultrasound to assess scoliosis has been well established previously [ 15 17 ], which agrees with this study: a good correlation between the ultrasound and radiographic assessment (r = 0.77). It is also found that the curve angle assessed by ultrasound was lower than that assessed by X-ray.…”
Section: Discussionsupporting
confidence: 92%
“…However, this comparison may not be feasible in the past because it requires X-ray taking at different body positions that exposes the patients to more radiation. An ultrasound technique would be an option for the radiation-free comparison since 3-D ultrasound (US) has been proved to be a reliable and valid technique to assess scoliosis [ 15 17 ]. Therefore, this study aims to investigate an effective assessment method of spinal flexibility to predict the initial in-orthosis correction using US technique.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2011) proposed to use the centre of lamina method (COL) to estimate the curvature and vertebral rotation of scoliosis. The method has subsequently been used [ 95 , 99 ] in a number of studies.…”
Section: D Ultrasoundmentioning
confidence: 99%
“…The feasibility and potential of using the 3D ultrasound imaging methods have been clearly demonstrated in recent studies for the measurement of scoliotic deformity in vivo [ 31 , 32 , 34 , 35 ] as well as for the improvement of brace fitting for scoliosis patients [ 36 , 37 ]. Being a radiation-free and cost-effective imaging modality, ultrasound imaging has potential to be widely used for scoliosis assessment; its popularity will be enhanced with improved portability of the ultrasound scanner.…”
Section: Introductionmentioning
confidence: 99%